The Influence of Family Emotional Support on the Quality of Life among the Elderly - Reza Saputra; Hendri Hadiyanto; Arfatul Makiyah; Asep Suryadin (Jurnal Keperawatan Priority, 2025)
The Central Statistics Agency reported a continued rise in the elderly population in Indonesia, indicating a growing demographic shift toward an aging society. Alongside this trend, a considerable proportion of older adults have been facing various health challenges. Many elderly individuals reported experiencing health problems within a recent period, reflecting a notable level of morbidity among this age group. The Central Statistics Agency of Sukabumi City noted, based on the results of the 2020 census, the elderly population in Sukabumi City amounted to 42,275 people and in Cibeureum sub-district there were 4,518 people and in Cibeureum Hilir Health Center there were 300 elderly people, using quantitative descriptive collegiate with a cross-sectional approach. the results of the static test using the chi-square p> value were 0.002 < 0.05 that the form of attention, assistance, enthusiasm and motivation from the family played a role in improving the quality of life of the elderly. So, it can be concluded that there is a relationship of family emotional support to the quality of life of the elderly in the working area of the Cibeureum Hilir Health Center, Sukabumi City. The researcher assumes that if each respondent receives good family support, their quality of life will be better. Conversely, if the emotional support from the family is lacking, it will negatively affect the elderly's quality of life.